Bacterial ghosts as carriers of protein subunit and DNA-encoded antigens for vaccine applications. (January 2012) - Muhammad, Abbas; Champeimont, Jonathan; Mayr, Ulrike Beate; Lubitz, Werner; Kudela, Pavol
Bacterial ghosts (BGs) represent vaccine delivery systems gifted with outstanding natural adjuvant properties. BGs are empty cell envelopes of Gram-negative bacteria lacking cytoplasmic content yet retaining all unaltered morphological and structural features of their living counterparts. The intact surface make-up of BGs is easily recognized by professional APCs through pattern-recognition receptors, making them ideal for mucosal administration through oral, ocular, intranasal or aerogenic routes, which represent the most desirable methods of application in advanced vaccine use. BGs have been designed to be used as carriers of active substances and foreign antigens (protein and/or DNA) for vaccine development. This review highlights the salient features of the BGs'' versatile multipurpose vaccine platform for application in a wide range of human and veterinary medicines.